New design of wireless ad-hoc network (WAHCN) for motorway monitoring system - Layth Abdulkareem Hassnawi (School of Computer and Communication Engineering, 2013)
In this thesis a newly designed motorway surveillance system network called Wireless Ad Hoc Camera Network (WAHCN) is proposed, modeled and analyzed. WAHCN enables motorway users to access image data taken by a network of cameras placed along the motorway. It provides improved safety awareness by allowing motorway users to view traffic and road conditions.